TERT, a promoter of CNS malignancies. Issue 2 (28th February 2020) - Patel, Bhuvic; Taiwo, Rukayat; Kim, Albert H; Dunn, Gavin P
Abstract: As cells replicate their DNA during mitosis, telomeres are shortened due to inherent limitations of the DNA replication process. Maintenance of telomere length is critical for cancer cells to overcome cellular senescence induced by telomere shortening. Telomerase reverse transcriptase (TERT) is the rate-limiting catalytic subunit of telomerase, an RNA-dependent DNA polymerase that lengthens telomeric DNA to maintain telomere homeostasis. TERT promoter mutations, which result in upregulation of TERT transcription, have been identified in several central nervous system (CNS) tumors, including meningiomas, medulloblastomas, and primary glial neoplasms. Furthermore, TERT promoter hypermethylation, which also results in increased TERT transcription, has been observed in ependymomas and pediatric brain tumors. The high frequency of TERT dysregulation observed in a variety of high-grade cancers makes telomerase activity an attractive target for developing novel therapeutics. In this review, we briefly discuss normal telomere biology, as well as the structure, function, and regulation of TERT in normal human cells. We also highlight the role of TERT in cancer biology, focusing on primary CNS tumors. Finally, we summarize the clinical significance of TERT promoter mutations in cancer, the molecular mechanisms through which these mutations promote oncogenesis, and recent advances in cancer therapies targeting TERT.